1970
DOI: 10.1002/bit.260120603
|View full text |Cite
|
Sign up to set email alerts
|

Microbial cell recovery enhancement through flocculation

Abstract: The removal of cellular material from fermentation broths is of importance in many fermentation processes. The present work compares the performance of recently developed polyelectrolyte flocculating additives with traditionally available additives. Objectives are to establish criteria for the choice of a flocculating additive and establish optimum conditions for the formation of stable, fast settling floc, and for quantitative separation of cellular material from the medium. Fermentation broths of actively gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…The one flocculant which produced a clear supernatant on centrifugaticm was anionic in nature, even though these cells have a negatively charged surface. This surprising result is in accordance with the conch&ns of Gamer and Wang (1970), who claimed an excess of multivalent cations and cationic macromolecules present in a normal broth form an adsorbed layer on the cell surface changing its flocculation properties. It has been consistently demonstrated that cationic polymers are far better flocculants than non-ionic or anionic polymers and Hughes et al, ( 1990) have shown that the natural cationic polyelectrolyte chitosan, is particularly effective.…”
Section: Introductionsupporting
confidence: 78%
“…The one flocculant which produced a clear supernatant on centrifugaticm was anionic in nature, even though these cells have a negatively charged surface. This surprising result is in accordance with the conch&ns of Gamer and Wang (1970), who claimed an excess of multivalent cations and cationic macromolecules present in a normal broth form an adsorbed layer on the cell surface changing its flocculation properties. It has been consistently demonstrated that cationic polymers are far better flocculants than non-ionic or anionic polymers and Hughes et al, ( 1990) have shown that the natural cationic polyelectrolyte chitosan, is particularly effective.…”
Section: Introductionsupporting
confidence: 78%
“…The precipitation is brought about by: a) electrostatic interaction between the negative charge of the surface of the cells and the positive charge of Primafloc C-7, b) the electrostatic interaction between the conglomerates formed under (a) and the Primafloc A-10 added later. 2 The precipitated material is successively extruded, dried at 56°C for 24 hr, and granulated. The heat treatment probably immobilizes the intracellular enzyme glucose isomerase inside the microorganism.3 After granulation cylinders are obtained of roughly m in diam and 4 x m in length (K.S.H.…”
Section: Structure Of the Catalyst Particlementioning
confidence: 99%
“…A classical study on the use of various types of flocculating agents for the yeast cell recovery was reported by Gasner and Wang (1970).…”
Section: Introductionmentioning
confidence: 99%